Mappalili: The Rice Planting Ritual of Bissu Part of Sustainable Environmental Agenda - Feby Triadi; Petsy Jessy Ismoyo; Nur Faidzaturrahmah; M. Awaluddin A; Fatma Utami Jauharoh (Journal of Public Representative and Society Provision, 2024)
Mappalili is a hereditary tradition carried out by the Segeri community in Pangkep Regency, South Sulawesi. This tradition is led by the Bissu in guiding the community as a sign that the cultivation of agricultural land (rice fields) has begun. This tradition is closely related to the understanding of Bugis cosmology in carrying out harmony between humans, nature, and the gods as creators. Mappalili contains a source of knowledge that is transmitted back through various symbols, movements, and ornaments used during ceremonies, but has begun to be overlooked. Therefore, this journal explores how the problems of the Bissu Community as an indigenous community play a role in socio-cultural development, related to the sustainable environmental agenda. This study uses an ethnographic method by involving direct participation with the Bissu community, observing their daily lives, conducting interviews, and utilizing other sources such as social context, kinship ties to patron-client relationships. This study shows that the Bissu community plays a role as a guardian of stability, namely social stability and ecological balance. They maintain the existence of noble values, and a strong relationship between humans, nature, and the gods that have been inherited from their ancestors. In conclusion, they play a key role in resisting external changes by maintaining local traditions. The symbols and movements in the Mappalili ritual highlight the ecological values held dear by the Bissu, which are closely interwoven with their spiritual and social beliefs.